C-Terminal PEGylation Improves SAAP-148 Peptide's Immunomodulatory Activities - Miriam E. van Gent; Bep Schonkeren-Ravensbergen; Asma Achkif; Daan Beentjes; Natasja Dolezal; Krista E. van Meijgaarden; Jan Wouter Drijfhout; Peter H. Nibbering (Karger Publishers, 2023)
Synthetic antibacterial and anti-biofilm peptide (SAAP)-148 was developed to combat bacterial infections not effectively treatable with current antibiotics. SAAP-148 is highly effective against antimicrobial-resistant bacteria without inducing resistance; however, challenges for further development of SAAP-148 include its cytotoxicity and short circulation half-life. To circumvent these drawbacks, a library of SAAP-148 linked to polyethylene glycol (PEG) groups of various lengths was synthesized and screened for in vitro antibacterial activity and hemolytic activity. Results indicated that PEGylated SAAP-148 variants combine antibacterial activities with reduced hemolysis compared to SAAP-148. Interestingly, proinflammatory immunomodulatory activities of SAAP-148 were enhanced upon C-terminal PEGylation, with SAAP-148-PEG27 showing the most effect. SAAP-148-PEG27 enhanced SAAP-148's capacity to chemoattract human neutrophils and was able to more efficiently (re)direct M-CSF-induced monocyte-macrophage differentiation toward type 1 macrophages as opposed to SAAP-148. Furthermore, dendritic cells with a stronger mature expression profile were produced if monocytes were exposed to SAAP-148-PEG27 during monocyte-immature dendritic cell differentiation in comparison to SAAP-148. Parameters that influenced the immunomodulatory activities of the peptide-PEG conjugate include (i) the length of the PEG group, (ii) the position of PEG conjugation, and (iii) the peptide sequence. Together, these results indicate that SAAP-148-PEG27 is highly effective in redirecting monocyte-macrophage differentiation toward a proinflammatory phenotype and promoting monocyte-mature dendritic cell development. Therefore, SAAP-148-PEG27 may be a promising agent to modulate inadequate immune responses in case of tumors and chronically infected wounds.